Layout of Release Works and Design of Revetment of Lagdo Hydropower Station - WANG Yi-zhui (Renmin Zhujiang)
The Lagdo Hydropower Station has a storage volume of 8.69 billion m3 and an installed capacity of 72 MW. The clay core rockfill dam is 40m high with its release works consisting of a spillway and a release outlet. The release outlet is arranged on the right bank of the main dam and is a free-flow tunnel for diversion, flood disposal and emptying the reservioir. The tunnel is in the form of an archway, with its mouth expanding toward both sides and dissipating energy by continuous deflector. Next comes the 550m long tailrace directing the flow into the main river bed. The spillway is 42m in width in average with bucket to dissipate energy. Behind the bucket is a 20m long apron. Situated on the left bank, the headrace channel is a structure for diversion, flood disposal, power generation and irrigation. After completion, it has been shown that the project layout is reasonable and the dam works satisfactorily in flood detention. However, scouring in different degrees has occurred downstream the spillway and the release runnel. In the light of this situation, a revetment has been designed and constructed. The revetment works well since putting into operation.